Awareness of typical speech-language development among parents of children with hearing impairment - Pallavi, Pooja; Waknis, Aarti P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Parents of children with hearing impairment who are aware of normal speech-language development play an effective and active role in the early detection, diagnosis, and habilitation of these children. Hence this study was aimed to explore the level of awareness about normal speech and language milestones in parents of children with hearing impairment. Methods: Questionnaire assessing the parents’ awareness of speech-language development in children from birth to 3 years was administered on 80 parents of children (birth to 5 years) with hearing impairment. These included 40 parents of children recently diagnosed with hearing impairment (group 1 HI-R) and 40 parents of children with hearing impairment who were fitted with appropriate hearing devices and enrolled in a speech and language habilitation program (group II HI-T). Results: Results indicated that the level of awareness was moderate for both the groups for semantic and morphosyntax domains as well as total scores, but was low to moderate for the pragmatic domain. There was no statistically significant difference in the level of awareness between the two groups. Conclusions: Moderate awareness levels indicates that parents of children with hearing impairment need to be made aware about the normal speech and language development so that it can guide them in the habilitation process. This information although important does not appear to have been provided to the parents of children already undergoing habilitation. Thus, there is need of including this as a goal in parental counseling.